Droplet spectrum and fungicide efficiency in the control of Asian soybean rust (Phakopsora pachyrhizi Syd. & P. Syd.) - Felipe Rafael Garcés-Fiallos; Anderson Luiz DuranteDanelli; Rosane Baldiga-Tonin; Walter Boller (Acta Agronómica)
The aim of this study was to evaluate the chemical control of Asian soybean rust (Phakopsora pachyrhizi Syd. & P. Syd.) using different tips and spray nozzles under controlled conditions. Rooted trifolia placed inside an acrylic box containing macronutrients, micronutrients and vitamins were treated with epoxiconazol + pyraclostrobin, ciproconazol + azoxystrobin and tebuconazol fungicides. These fungicides were sprayed at a height of 0.5 m with two knapsack sprayers pressurized with CO2 gas (drop generator in four spray tips spaced by 0.5 m from each other) and another rotating nozzle (drop generator through a rotating nozzle). Untreated trifolia were controls. Water sensitive paper was placed next to each acrylic box to obtain median volume diameter (MVD), number of droplets.cm-2 and coverage (%). Trifolia were inoculated 24 hours after that these were treated with fungicide, using a spore concentration adjusted to 2 x 104 uredospores.mL-1. Then, the number of lesions and uredia.cm-2 in central leaflets were quantified. Lower number of lesions and uredia.cm-2 were observed in leaflets treated with two fungicide mixtures using an AIRMIX 11001 tip. A lower VMD was found in leaflets sprayed with the fungicides azoxystrobin + epoxiconazol and tebuconazol, when compared to the leaflets treated with another mixture. The Asian rust control, as well as the number of droplets.cm-2 and coverage, seems to be dependent on the interactions among fungicides and tips or nozzles.